2014
DOI: 10.6004/jnccn.2014.0080
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Stromal Tumors, Version 2.2014

Abstract: Gastrointestinal stromal tumors (GIST) are the most common soft tissue sarcoma of the gastrointestinal tract, resulting most commonly from KIT or platelet-derived growth factor receptor α (PDGFRα)-activating mutations. These NCCN Guideline Insights highlight the important updates to the NCCN Guidelines for Soft Tissue Sarcoma specific to the management of patients with GIST experiencing disease progression while on imatinib and/or sunitinib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
99
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 25 publications
5
99
0
1
Order By: Relevance
“…Imatinib treatment may be considered preoperatively in order to inhibit tumor activity, and works by minimizing the tumor load and eliminating potential satellite lesions (21). Post-operatively, imatinib may be administered for adjuvant treatment for patients with a high recurrence risk, which is similar to the guidelines for their alimentary counterparts (22). Although imatinib exhibits a satisfactory curative effect in certain cases (11,16), the clinical value of imatinib on primary liver GISTs requires verification.…”
Section: Discussionmentioning
confidence: 99%
“…Imatinib treatment may be considered preoperatively in order to inhibit tumor activity, and works by minimizing the tumor load and eliminating potential satellite lesions (21). Post-operatively, imatinib may be administered for adjuvant treatment for patients with a high recurrence risk, which is similar to the guidelines for their alimentary counterparts (22). Although imatinib exhibits a satisfactory curative effect in certain cases (11,16), the clinical value of imatinib on primary liver GISTs requires verification.…”
Section: Discussionmentioning
confidence: 99%
“…There are certain differences in the follow-up examinations after surgery for GISTs between the guidelines of the National Comprehensive Cancer Network (NCCN) and the Japanese Society of Clinical Oncology (JSCO) (14,15). After surgical resection of all tumors, the NCCN guidelines recommend abdominal and pelvic CT imaging every 3-6 months for 3-5 years.…”
Section: Discussionmentioning
confidence: 99%
“…[5,7,8,9] Surgery accompanied by adjuvant radiotherapy as needed is the gold standard for achieving local control of STS. [3,5,7,[9][10][11][12] The role of chemotherapy in the cure of STS is underrecognized, but it is currently improving. [5,13] The aim of surgery and radiotherapy is local control of the STS, whereas the aim of chemotherapy is systemic control as curative, supportive, or palliative therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[2,5,6] Some sarcomas are more likely to develop with genetic syndromes that have been associated with the pathogeny of STS, such as retinoblastoma syndrome, Li-Fraumeni syndrome, and familial adenomatous polyposis. [2,3,5,6] Recent studies have indicated that grade, tumor size, surgical margins, histology, location, radiotherapy, age, and sex are important prognostic factors for STS. [5,7,8,9] Surgery accompanied by adjuvant radiotherapy as needed is the gold standard for achieving local control of STS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation